Predicting perioperative venous thromboembolism in Japanese gynecological patients. - Masae Ikeda; Hidetoshi Kan-no; Masaru Hayashi; Hitomi Tsukada; Masako Shida; Takeshi Hirasawa; Toshinari Muramatsu; Yoichi Ogushi; Mikio Mikami (PLoS ONE, 2014)
Objective To develop a convenient screening method that can predict perioperative venous thromboembolism (VTE) and identify patients at risk of fatal perioperative pulmonary embolism (PE). Methods Patients hospitalized for gynecological abdominal surgery (n = 183) underwent hematology tests and multidetector computed tomography (MDCT) to detect VTE. All statistical analyses were carried out using the SPSS software program (PASWV19.0J). Results The following risk factors for VTE were identified by univariate analysis: plasmin-alpha2-plasmin inhibitor complex (PIC), thrombin-antithrombin III complex (TAT), and prolonged immobility (all p<0.001); age, neoadjuvant chemotherapy (NAC), malignancy, hypertension, past history of VTE, and hormone therapy (all p<0.01); and hemoglobin, transverse tumor diameter, ovarian disease, and menopause (all p<0.05). Multivariate analysis using these factors revealed that PIC, age, and transverse tumor diameter were significant independent determinants of the risk of VTE. We then calculated the incidence rate of perioperative VTE using PIC and transverse tumor diameter in patient groups stratified by age. In patients aged ≤40 years, PIC ≥1.3 µg/mL and a transverse tumor diameter ≥10 cm identified the high-risk group for VTE with an accuracy of 93.6%. For patients in their 50 s, PIC ≥1.3 µg/mL identified a high risk of VTE with an accuracy of 78.2%. In patients aged ≥60 years, a transverse tumor diameter ≥15 cm (irrespective of PIC) or PIC ≥1.3 µg/mL identified the high-risk group with an accuracy of 82.4%. Conclusions We propose new screening criteria for VTE risk that are based on PIC, transverse tumor diameter, and age. Our findings suggest the usefulness of these criteria for predicting the risk of perioperative VTE and for identifying patients with a high risk of fatal perioperative PE.